2017 Year-End Editorial - Heng Hartse, Joel (Discourse and Writing/Rédactologie, 2018)
Traditionally, the editorial note for an issue or volume of a journal would start on page 1—or even page I—but one of the unique things about an article-based, open access publishing model is that we assemble the issue on the go—so rather than “introducing” Vol. 27 of the CJSDW/R, I find myself writing this note to “wrap up” the issue.